2015
DOI: 10.1038/ncomms7723
|View full text |Cite
|
Sign up to set email alerts
|

Twisting phonons in complex crystals with quasi-one-dimensional substructures

Abstract: A variety of crystals contain quasi-one-dimensional substructures, which yield distinctive electronic, spintronic, optical and thermoelectric properties. There is a lack of understanding of the lattice dynamics that influences the properties of such complex crystals. Here we employ inelastic neutron scatting measurements and density functional theory calculations to show that numerous low-energy optical vibrational modes exist in higher manganese silicides, an example of such crystals. These optical modes, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
72
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 56 publications
14
72
1
Order By: Relevance
“…The magnitude of the anisotropy is similar to that found for layered Bi 2 Te 3 242526 and higher than that of manganese silicide (HMS)27. While significant bonding anisotropy was held responsible for the anisotropic κ in Bi 2 Te 3 28 with van der Waals gaps in the low κ direction, a low-energy (<10 meV) twisting phonon and anisotropic group velocity of the optic phonons were found responsible for the observed κ anisotropy in HMS27. We note that Lee et al 5.…”
Section: Resultssupporting
confidence: 76%
“…The magnitude of the anisotropy is similar to that found for layered Bi 2 Te 3 242526 and higher than that of manganese silicide (HMS)27. While significant bonding anisotropy was held responsible for the anisotropic κ in Bi 2 Te 3 28 with van der Waals gaps in the low κ direction, a low-energy (<10 meV) twisting phonon and anisotropic group velocity of the optic phonons were found responsible for the observed κ anisotropy in HMS27. We note that Lee et al 5.…”
Section: Resultssupporting
confidence: 76%
“…At present, significant efforts have been focused on decreasing the κ tot of HMS. Shi and co‐workers19, 20 demonstrated that κ tot can be decreased to 2.2 W m −1 K −1 at 773 K when certain 50–200 nm ReSi 1.75 precipitates formed in the HMS samples; consequently, ZT increased from 0.45 to 0.57. Takeuchi and co‐workers21 proved that κ tot can be further decreased to 1.8 W m −1 K −1 at 773 K when 6.0 at% Re was used to form a supersaturated Re solid solution HMS, and the corresponding ZT value increased to 0.9 at 773 K. In our previous work,22 Te nanowires were selected to prepare MnTe/HMS nano/bulk structures, resulting in 38% reduction of κ tot and ≈71% increase in ZT .…”
mentioning
confidence: 99%
“…Current efforts to improve zT are focused on the optimization of power factor α 2 σ through controlled doping or electron band engineering,7, 8, 9, 10, 11 suppression in κ L by alloying or nanostructuring,1, 2, 5, 6 and development of new materials with intrinsically low κ L 12, 13, 14, 15. Heat‐carrying phonons cover a broad spectrum of frequency, and the κ L is a sum of contributions from phonons of different frequencies.…”
mentioning
confidence: 99%